Design and Synthesis of Novel 1, 2, 3‐Triazole‐ and 2‐Isoxazoline‐Based Bis‐Heterocycles as Immune Potentiators. Issue 11 (23rd September 2015) - Ismail, Tabasum; Shafi, Syed; Hyder, Irfan; Sidiq, Tabasum; Khajuria, Anamika; Alam, Sarvar M.; Halmuthur, M. Sampath Kumar
Abstract : A series of novel bis ‐heterocycles encompassing isoxazolines and triazoles were synthesized through a novel one‐pot procedure that involves in situ generation of nitrile oxide and its 1, 3‐dipolar cycloaddition to variedly substituted acrylates. The synthesized bis ‐heterocycles (8a –l ) were subjected to in vitro lymphocyte proliferation assays followed by in vivo studies of the more active compounds (8g and8h ) to assess their influence on various aspects of the immune system like ex vivo splenocyte proliferation (T‐ and B‐cell proliferation), antibody production (HA titer), delayed‐type hypersensitivity reaction, T‐cell subtypes (CD4 and CD8), cytokine production (IL‐2, IFN‐γ, and IL‐4), NO (macrophage) production, and toxic effects. The results from the in vitro and in vivo studies establish that the tested compounds8g and8h possess excellent immunopotentiating activity. Abstract : A series of bis ‐heterocycles bearing triazole and isooxazoline are synthesized and subjected to in vitro lymphocyte proliferation assays, followed by in vivo studies of the more active compounds, 8g and8h . Based on both the in vitro and in vivo studies, compounds8g and8h possess excellent immunopotentiating activity.